Health Metrics of P.E. Teachers from Direct and Smart Phones App Measurements: Their Relationship with Gender, Age, and Areas Handled - Eliza B. Ayo; Anabel G. Lim; Rosalie P. Alejandro; Richard Niel B. Peralta; Raymond L. Peralta; Ma. Christina A. Florentino; Joel H. Cruz; Jean Bernadette C. Parcher (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the relationship between demographic and professional factors—specifically gender, age, and physical education (P.E.) areas handled—and health and sleep metrics among P.E. teachers. A quantitative cross-sectional design was employed among 374 P.E. teachers. Data were collected using validated instruments, including the Pittsburgh Sleep Quality Index (PSQI) and International Physical Activity Questionnaire (IPAQ), along with direct and smart app health measurements. Statistical analyses included independent t-tests, Pearson correlations, ANOVA, and chi-square tests. The sample comprised 58.8% males with a mean age of 38.9 years. Gender showed minimal relationships with health metrics except for daily steps (females higher, p = 0.05). Age was significantly associated with sleep quality (r = 0.15, p = 0.03), sleep disorder prevalence (χ2 = 10.5, p = 0.03), BMI category (χ2 = 12.3, p = 0.02), and blood pressure (systolic: r = 0.20, p = 0.01; diastolic: r = 0.18, p = 0.02). Most notably, P.E. areas handled showed the strongest associations with health metrics, particularly physical activity levels, daily steps, sleep quality, and BMI categories (all p < 0.05). Professional specialization within P.E. teaching emerged as the most significant predictor of health and sleep outcomes, surpassing demographic factors. These findings inform institution for targeted wellness interventions to revisit and review institutional policies for P.E. educators.